Application of Paraffin Based Nanocomposite in Heat Pipe Module for Electronic Equipment Cooling. (2018) - Chougule, Sandesh S.; Nirgude, Vishal V.; Shewale, Sapana P.; Pise, Ashok T.; Sahu, S.K.; Shah, Hardik
Abstract: The paper reports the thermal performance of heat pipe module with paraffin and paraffin based nanocomposites as energy storage material (ESM) for electronic cooling. The adiabatic section of heat pipe is covered by the phase change material (PCM) stored in a container made of acrylic material. Here, paraffin is used as phase change material (PCM). PCM can absorb and release thermal energy depending upon the fluctuations in the heating load. Tests are conducted to obtain the temperature distributions in PCM during charge/discharge processes. Present study utilizes two different ESM (paraffin and nanocomposite) and different working fluid for heat pipe (water and nanofluid) in the cooling module. The addition of CNTs in paraffin stores higher amount energy compared pure paraffin material for same operating conditions. The cooling module with nanofluid charged heat pipe and paraffin as ESM found to save higher fan power consumption compared to the cooling module that utilizes only a heat pipe